Handbook of molecular and cellular methods in biology and medicine - Cseke, Leland J. (CRC Press/Taylor & Francis Group, 2011)
"Reflecting the milestones in the field that have occurred since the publication of the first edition, this book provides an updated tool kit that incorporates conventional as well as modern approaches to tackling biological and medicinal research in the post genomic era. The authors have evaluated, revised, and sometimes replaced all protocols with more efficient, reliable, or simpler ones. The book is also completely reorganized and covers topics of modern "omics" approaches, including genomics, proteomics, and metabolomics. This is followed coverage of the Manipulation of Biological Systems, including RNAi, and the use of microscopy"--Provided by publisher.